The Spine Physical Examination Using Telemedicine: Strategies and Best Practices - Sravisht Iyer; Karim Shafi; Francis Lovecchio; Robert Turner; Todd J. Albert; Han Jo Kim; Joel M. Press; Yoshihiro Katsuura; Harvinder S. Sandhu; Frank Schwab; Sheeraz A. Qureshi (2020)
Technical note.To provide spine surgeons new to telemedicine with a structured physical examination technique based on manual motor testing principles.Expert experience describing a series of specific maneuvers for upper and lower extremity strength testing that can be performed using a telemedicine platform. In addition, we offer instruction on "setting up" for these visits and highlight special tests that can be used to diagnose specific cervical and lumbar spine conditions.From our experiences in conducting telemedicine visits, we provide a means of testing and scoring upper and lower extremity strength for interpretation of weakness in the context of traditional manual motor testing. Also, we acknowledge the limitations of a remote examination and discuss maneuvers that cannot be performed remotely.COVID-19 has drastically altered the delivery of care for patients with spine-related complaints. The need for social distancing has led to the widespread adoption of telemedicine. This technical note provides an urgently needed framework for the standardization of the remote physical exam. Validation of the exam as a diagnostic tool will be a crucial next step in studying the impact of telemedicine.